(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article summarizes theoretical and practical research in the higher education system of the Republic of Uzbekistan and offers a new solution to the problem of improving the quality of humanities teacher training identified in the creation of psychological and pedagogical sciences. Information about creating conditions for the development of effective pedagogical thinking of pedagogues is provided. Principles of implementation of psychological tools and pedagogical conditions, methods, stages and goals of developing effective pedagogical thinking are analyzed. We conducted an experiment and determined the levels of formation of effective pedagogical thinking of students. Based on the indicators, we determined the main levels maturity of effective pedagogical thinking of future teachers in the process of learning humanities. The results of the experiment showed positive dynamics in the change of maturity level of effective pedagogy. We have provided information about the essence of pedagogical principles at the stages of development of students’ thinking level.